Between Q and M, x changes +2 from 3 to 5. It has to change the same amount from M to P, so the new x is 5 + 2 = 7.
Between Q and M, y changes +5 from -3 to 2. The same amount of change means that the new y is 2 + 5 = 7.
P (7,7)
Easiest way to solve this problem would be to graph M and Q so that you could visualize it.
Aloha
2006-09-10 17:09:56
·
answer #1
·
answered by Anonymous
·
2⤊
0⤋
Ok, so this is the opposite of the other problem. You have the midpoint and one pont, but you need the other point.
Lets call the coordinates of p as (x2, y2), ok.
The midpoint is the average of the two x and two y coordinates.
For the x coordinates:
If its the average, that means that
(x2+3)/2 = 5. Multiply Both sides by 2
(x2+3) = 5 X 2
x2+ 3 = 10 Subtract 3 from both sides
x2 = 7
for the y coordinates
(y2 + -3) /2 = 2 - Multiply both sides by 2
(y2+ -3) = 2 X 2
y2 - 3 = 4 - Add 3 to both sides
y2 = 7
So Point p is (7,7)
2006-09-10 17:07:56
·
answer #2
·
answered by Manan T 3
·
0⤊
0⤋
Given end factors of pq are p ( -7 , 12 ) = p( X1 , Y1 ) q ( 3 , - 2 ) = q( X2 , Y2 ) enable the midpoint = r ( X , Y ) We get X= ( X1 + X2 ) / 2 = (- 7 + 3) / 2 = - 4 / 2 = - 2 Y= ( Y1 + Y2 ) / 2 = ( 12 - 2 ) / 2 = 10 / 2 = 5 So the midpoint is r ( X , Y ) = r ( - 2 , 5 ) i wish this supplies you with a sparkling theory .
2016-11-26 00:28:55
·
answer #3
·
answered by nevius 4
·
0⤊
0⤋
You can find the x and y coordinates of the midpoint independently. This makes the problem a lot easier.
Think of it this way: Since M is half way between P and Q, its x coordinate must be half way between the x coordinates of P and Q, and its y coordinate must be half way between the y coordinates of P and Q.
So since the x coordinate of Q is 2 less than the x coordinate of M, the x coordinate of P must be 2 more than the x coordinate of M. Similarly the y coordinate of Q is 5 less than the y coordinate of M, so the y coordinate of P must be 5 more than the y coordinate of M.
You can use this reasoning to find the answer.
2006-09-10 17:04:38
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
7,7? mabey so subtract 3 from 5 and then 2 from -3 then ad those to the orriginal coordinates... lol i hope i got it right its been years since ive done this..
2006-09-10 17:06:33
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(x1+3)/2=5=>x1=7
(y1+(-3))/2=5=>y1=7
so finally P(7,7)
2006-09-10 17:09:25
·
answer #6
·
answered by optik 1
·
0⤊
0⤋
x = (x2 + x1)/2
y = (y2 + y1)/2
5 = (x2 + 3)/2
10 = x2 + 3
x2 = 7
2 = (y2 - 3)/2
4 = y2 - 3
y2 = 7
ANS : P(7,7)
2006-09-10 19:05:16
·
answer #7
·
answered by Sherman81 6
·
0⤊
0⤋
it's (7,7)
2006-09-10 18:57:34
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋